The Contributions of Imam Shatibi in Serving the Science of Prophetic Traditions: denotatively, inferentially, and traceably - BOUKHAF , djamel eddine (Journal of Social Sciences and Humanities, 2025)
The present paper tackles one aspect of the fundamentalist renewal of Imam Al-Shatibi, namely the Prophetic traditions and related aspects of fundamentalists, that are far away from the hadith and jurisprudential issues, all of which are the raw material for the sciences of the Prophetic Sunnah. Imam Al-Shatibi's contribution was reflected through three issues: denotation, tracing the origin, and inference, that were also approved by fundamentalists before him. As for the concept of Prophetic traditions and its appendices, Imam Shatibi approved of what was previously agreed upon, and added a prominent elucidation backed by clear texts. As far as tracing origins is concerned, Imam Shatibi followed a special approach therewith. That is to say, he renewed the approach and created rules of referring to meanings of the Sunnah to the Holy Qur’an, and then proposed a piece of evidence for that. This is to confirm the stability of the adopted approach and to validate the authenticity of the real knowledge of Prophetic traditions, distinguishing between general rulings and specific meanings of the prophetic Sunnah, as well as the rulings enshrined therewith. Thus, the prophetic Sunnah may be independent when comes to mention the second without the first, for it is heavily related to Quranic meanings. With regard to inference based on Sunnah and its general rulings and meanings, Imam Shatibi did not deviate from the already approved decisions, he, however, discussed the frowned upon notions, and then delineate its reality. This contribution has demystified many controversies and aborted many false statements on this regard. He, then, discussed the notion of solitary (isolated reports), reiterating its explicit authority, and that part of it came from a definitive origin and some others are from a conjectural meaning. He also discussed the notion of the significance of the Prophetic action, which was very controversial. In that, he analysed the matter from a fundamentalist perspective, and determined afterwards what is agreed and frowned upon, and decided to marginalize so many fundamentalist controversies, and proposed statements that were resulted from a misunderstanding of the correct perception. He then suggested new corrections and meanings using a well-put fundamentalism approach that brilliantly serves the purpose.